Work Life Balance among Female School Teachers Delivering Online Curriculum in Bandgaon Block During COVID-19: An Empirical Study - Jayant Kumar Sahoo; Vijay Prakash (Ridwan Institute, 2023)
Work life balance today, in particular in instances of COVID the place home and work place have transgressed boundaries is an indispensable precursor for the well-being of an individual. Increased female employment has led to a swelling interest from academia and industry on WLB. With higher access to better educational opportunities, growing number of female are coming into the workforce, and moving from being home-makers to the geared up work force, thereby necessitating an urgent need to observe this phenomenon. Carrying on with on line lessons remotely has grown to be the order of the day, and it is turning into worrying when each school and personal life operate from the same space. The predominant idea here is to recognize challenges at some point of COVID which are being confronted with the aid of school teachers in Bandgaon block delivering content to students from home and their surviving strategies. A combination of 150 fermale teachers’ responses are covered in the study. Average literacy rate of Bandgaon Block in 2011 had been 54.46 in which, man and female literacy had been 69.02 and 39.95 respectively. Total literate in Bandgaon Block have been 805 of which man and woman have been 547 an 258 respectively. This study also identifies primary problems and challenges which confronted by unwedded and wedded working female in Covid-19. Both Telephonic and Online interview are taken to fulfill the objectives. Random sampling technique used to be used for collection of primary data through Telephinic and Online interviews.